LANDSCAPE ELEMENTS SYMBOLISM IN MUSEUM PURNA BHAKTI PERTIWI, JAKARTA - Intanasia Noorardi; Hinijati Widjaja; Rini Fitri; Eko Adhy Setiawan (Journal of Synergy Landscape, 2022)
Purna Bhakti Pertiwi Museum is a museum that was established as a manifestation of the gratitude of Soeharto and his family to God Almighty, as well as appreciation for the support given by the Indonesian people and abroad. The form of gratitude is depicted through the concept of symbolism applied to the museum area, one of which is through landscape elements. Symbolism is a concept of human thought that is realized through symbols. Collecting data in this study using the interview method and identifying the symbolism contained in the elements of the museum landscape using Symbolism in Javanese culture which is classified into Symbolism in Religion, Symbolism in Culture, and Symbolism in Science. Based on this research, it was revealed that the landscape element was used as a way for him to be grateful for the blessings and safety bestowed by the Creator, an effort to respect and preserve the culture of his ancestors as a Javanese person, and as a medium of education for the Indonesian people.